The effectiveness of telehealth on self-management for older adults with a chronic condition: A comprehensive narrative review of the literature. (July 2018) - Guo, Yuqi; Albright, David
Introduction: Given the rapid global growth of older adults with chronic condition(s), the present study explored the effects of telehealth technologies on self-management among older adults with chronic condition(s). Methods: Clinical trial studies on telehealth self-management for older adults with chronic condition(s) published in peer reviewed journals were reviewed systematically. In addition, the potential biases were assessed for included studies. Results: This review identiﬁed 31 articles regarding the effectiveness of telehealth technologies on self-management among older adults. Discussion: According to the findings of the present study, telehealth technologies have shown effectiveness on improving self-care skills, improving self-monitoring behaviours and improving clinical outcomes among older adults with chronic condition(s) in different settings. Using telehealth technologies is an advisable intervention for promoting older patients' self-management. However, it is critical to consider racial diversity and culture-related health behaviour differences when using telehealth technologies.